2017
DOI: 10.4274/tjps.81994
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of Vitronectin, Soluble Epithelial-Cadherin and TGF-β1 as a Serum Biomarker with Predictive Value for Endometrial and Ovarian Cancers

Abstract: ÖZAmaç: Vitronektin, çözünür epitelyal-cadherin (sE-cadherin) ve transforming büyüme faktörü-beta 1'i (TGF-β1) içeren ekstrasellüler matriks elemanları kanserin invazyonu ve metastazında anahtar rol oynamaktadır. Bu çalışmada endometriyal ve over kanserli hastalarda bu moleküllerin serum düzeylerinin klinik önemini belirlemek amaçlanmıştır. Gereç ve Yöntemler: Bu çalışmada, 28 endometriyum kanseri hastası, 40 over kanseri hastası ve 41 sağlıklı kontrol grubuna ait serum vitronektin (VN), sE-cadherin ve TGF-β1 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
4
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 39 publications
1
4
0
Order By: Relevance
“…It has been pointed out that vitronectin plays an important role in pathophysiological processes and its biosynthesis can be regulated during disease progression. By using ELISA approach, a significant decrease of vitronectin in serum of patients with endometrial and ovarian cancer was observed (Turan et al 2017). Similar reduced concentration in breast cancer samples was figured out, elsewhere (Kim et al 2009).…”
Section: Discussionsupporting
confidence: 75%
See 1 more Smart Citation
“…It has been pointed out that vitronectin plays an important role in pathophysiological processes and its biosynthesis can be regulated during disease progression. By using ELISA approach, a significant decrease of vitronectin in serum of patients with endometrial and ovarian cancer was observed (Turan et al 2017). Similar reduced concentration in breast cancer samples was figured out, elsewhere (Kim et al 2009).…”
Section: Discussionsupporting
confidence: 75%
“…Similarly as in E-cadherin, vitronectin protein exhibited lower concentration in endothelial cancer patients (ECP) than in control group as seen in Figure 3. Vitronectin is a main plasma glycoprotein with multiple functions including regulation of cell differentiation, proliferation and morphogenesis (cell adhesion molecule) (Turan et al 2017). It also belongs among the major components of the extracellular matrix together with collagens, laminin and fibronectin.…”
Section: Discussionmentioning
confidence: 99%
“…Kadowaki et al in their study demonstrated that vitronectin expression was significantly elevated in the serum of early and more advanced breast cancer patients compared to normal controls [18]. Turan et al have proposed vitronectin as a marker in ovarian cancer [19]. Figure 3 shows that the precipitation method provides higher SC of the keratin family proteins and albumin.…”
Section: Resultsmentioning
confidence: 98%
“…The expression of versican does have an impact on survival in correlation with infiltration depth. In patients with cervical cancer with an infiltration depth greater than 15 mm, low expression of versican predicts poorer survival [ 41 , 42 ].…”
Section: Resultsmentioning
confidence: 99%
“…Their adhesive characteristics play an important role in cell rearrangement, sorting, and migration [ 40 ]. Several studies have shown that lower cadherin expression is associated with extensive tumour invasion and metastasis in endometrial, ovarian, and cervical cancers [ 42 ].…”
Section: Resultsmentioning
confidence: 99%